Code Comment Analysis–A Review Paper - Syed Zohaib Hassan; Ayesha Irshad; Jamaluddin Mir; Ayesha Aslam; Kalsoom Ayaz; Muhammad Awais Bawazir (Journal of Management Practices, Humanities and Social Sciences, 2022)
The compilers are manufactured in such a way that they ignore most comments in software systems' source code. In addition to being a key source of system documentation, code comments are essential for both establishment and improvement. System comments or just quantitative assertions regarding the quality of the program are presently the only known techniques for evaluating software quality. In software development, comments are being used as a regular practice to enhance the clarity of code and to transmit the enthusiasm of programmers in a more conveyed manner. Whereas programmers seldom bother to keep their comments current. Comments are an important source of information about how the framework works. Various disciplines have concentrated on the content of the online client comments in different contexts, utilizing manual quantitative/subjective or (semi-)automatic methods. The wide variety and disciplinary partitions make it hard to get a handle on an outline of those views which have proactively been inspected. The huge number of daily comments inundating the newsroom can be amazing, particularly when a huge chunk is unfriendly or